Hungarian Monitoring, 11 August 1988 . [Magyar rádiófigyelő], 1988. augusztus 11 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Neo-Fascist tendencies in the USSR - Refugees from Romania now also arriving in Yugoslavia - Yugoslav intellectuals discuss Tito's responsibility Domestic Affairs: - Ministerial council in session; new government spokesman appointed - Hungarian UN soldiers in Iraq-Iran peacekeeping forces - The Gabčíkovo-Nagymaros case - Unemployment - Railway development plans - Prospects for legal rehabilitation of Hungarians convicted in the USSR Economy: - Deputy minister for trade holds press conference Külpolitika: - Újfasiszta irányzatok a Szovjetunióban - Jugoszláviába is érkeznek menekültek Romániából - Tito felelősségéről beszélnek jugoszláv értelmiségiek Belpolitika: - A Minisztertanács ülése; új kormányszóvivői kinevezés - Magyar ENSZ katonák az iraki-iráni tűzszünet fenntartásában - A Bős-nagymarosi vízlépcső ügye - Munkanélküliség - Vasútfejlesztési tervek - Kilátásban a Szovjetunióban elítélt magyarok jogi rehabilitása Gazdaság: - A kereskedelmi miniszterhelyettes sajtótájékoztatója